A systematic literature review of alcohol education programmes in middle and high school settings (2000-2014). Issue 1 (4th January 2016) - Dietrich, Timo; Rundle-Thiele, Sharyn; Schuster, Lisa; Connor, Jason P.
Abstract : Purpose: – Social marketing benchmark criteria were used to understand the extent to which single-substance alcohol education programmes targeting adolescents in middle and high school settings sought to change behaviour, utilised theory, included audience research and applied the market segmentation process. The paper aims to discuss these issues. Design/methodology/approach: – A systematic literature review retrieved a total of 1, 495 identified articles; 565 duplicates were removed. The remaining 930 articles were then screened. Articles detailing formative research or programmes targeting multiple substances, parents, families and/or communities, as well as elementary schools and universities were excluded. A total of 31 articles, encompassing 16 qualifying programmes, were selected for detailed evaluation. Findings: – The majority of alcohol education programmes were developed on the basis of theory and achieved short- and medium-term behavioural effects. Importantly, most programmes were universal and did not apply the full market segmentation process. Limited audience research in the form of student involvement in programme design was identified. Research limitations/implications: – This systematic literature review focused on single-substance alcohol education programmes targeted at middle and high school student populations, retrieving studies back to the year 2000. Originality/value: – The results of this systematic literature review indicate that application of the social marketing benchmark criteria of market segmentation and audience research may represent an avenue for further extending alcohol education programme effectiveness in middle and high school settings.